A NOVEL OF PUSHKIN "EUGENE ONEGIN" - Davlatova Noila; Nafisa Ochilova (Ta'lim innovatsiyasi va integratsiyasi, 2024)
"Eugene Onegin" explores themes of love, personal growth, social conventions, and the clash between idealism and reality. It is renowned for its lyrical beauty, psychological depth, and social commentary. Pushkin's innovative use of verse and his realistic portrayal of characters and society have made "Eugene Onegin" a timeless classic that continues to captivate readers around the world.